Finding Common Ground in Meta-Analysis "Wars" on Violent Video Games. (July 2019) - Mathur, Maya B.; VanderWeele, Tyler J.
Independent meta-analyses on the same topic can sometimes yield seemingly conflicting results. For example, prominent meta-analyses assessing the effects of violent video games on aggressive behavior have reached apparently different conclusions, provoking ongoing debate. We suggest that such conflicts are sometimes partly an artifact of reporting practices for meta-analyses that focus only on the pooled point estimate and its statistical significance. Considering statistics that focus on the distributions of effect sizes and that adequately characterize effect heterogeneity can sometimes indicate reasonable consensus between "warring" meta-analyses. Using novel analyses, we show that this seems to be the case in the video-game literature. Despite seemingly conflicting results for the statistical significance of the pooled estimates in different meta-analyses of video-game studies, all of the meta-analyses do in fact point to the conclusion that, in the vast majority of settings, violent video games do increase aggressive behavior but that these effects are almost always quite small.